Current positions regarding the diagnosis and screening of colorectal cancer and precancerous changes of bowel. Analysis of clinical cases - Yu.M. Stepanov; O.M. Vlasova; I.Y. Budzak (Gastroenterologìa)
The article deals with the problem of colorectal cancer and precancerous changes of bowel. Risk factors, clinical symptoms, diagnostic methods, directions for the prevention of colorectal cancer and precancer are considered. Three clinical cases of patients with bowel tumors and precancerous conditions are given and analyzed. The article places special emphasis on the need for timely detection of tumors and screening for colorectal cancer. Screening options are shown, each of the screening methods is analyzed. Screening algorithms based on the practical guidelines of different countries are given. The relevance and importance of the problem of colorectal cancer and precancerous changes are emphasized.